Validation of a Single Item to Assess Daytime Sleepiness for the Swiss Transplant Cohort Study. (September 2013) - Burkhalter, Hanna; Wirz-Justice, Anna; Cajochen, Christian; Weaver, Terri; Steiger, Jürg; Fehr, Thomas; Venzin, Reto Martin; De Geest, Sabina
Context: Daytime sleepiness in kidney transplant recipients has emerged as a potential predictor of impaired adherence to the immunosuppressive medication regimen. Thus there is a need to assess daytime sleepiness in clinical practice and transplant registries. Objective: To evaluate the validity of a single-item measure of daytime sleepiness integrated in the Swiss Transplant Cohort Study (STCS), using the American Educational Research Association framework. Methods: Using a cross-sectional design, we enrolled a convenience sample of 926 home-dwelling kidney transplant recipients (median age, 59.69 years; 25%-75% quartile [Q25-Q75], 50.27–59.69), 63% men; median time since transplant 9.42 years (Q25-Q75, 4.93–15.85). Daytime sleepiness was assessed by using a single item from the STCS and the 8 items of the validated Epworth Sleepiness Scale. Receiver operating characteristic curve analysis was used to determine the cutoff for the STCS daytime sleepiness item against the Epworth Sleepiness Scale score. Results: Based on the receiver operating characteristic curve analysis, a score greater than 4 on the STCS daytime sleepiness item is recommended to detect daytime sleepiness. Content validity was high as all expert reviews were unanimous. Concurrent validity was moderate (Spearman ϱ, 0.531; P < .001) and convergent validity with depression and poor sleep quality although low, was significant (ϱ, 0.235; P < .001 and ϱ, 0.318, P = .002, respectively). For the group difference validity: kidney transplant recipients with moderate, severe, and extremely severe depressive symptom scores had 3.4, 4.3, and 5.9 times higher odds of having daytime sleepiness, respectively, as compared with recipients without depressive symptoms. Conclusion: The accumulated evidence provided evidence for the validity of the STCS daytime sleepiness item as a simple screening scale for daytime sleepiness.